Species Diversity and Feeding Guilds of Birds as Potential Resources for Birdwatching Ecotourism in Napabale Lake, Southeast Sulawesi - La Ode Muhammad Jabarudin; Amirullah Amirullah; Adi Karya (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2026)
The Napabale Lake Tourism Area in Muna Regency, Southeast Sulawesi, possesses a unique ecosystem formed by the interaction between the lake and marine environments, supported by diverse vegetation that provides habitat and food resources for various bird species. Bird diversity across different habitats is important to study in order to understand community structure and its ecological potential. This study aims to identify bird species diversity and the composition of feeding guilds within the Napabale Lake ecosystem as a basis for ecological information and the potential development of birdwatching-based ecotourism. The study was conducted using the point-count method across three ecosystem types: lowland forest, lake riparian, and coastal areas. Observations were conducted in the morning (06:00–08:30 WITA) and afternoon (15:00–17:30 WITA), with three repetitions in each ecosystem over nine days of observation. Data were analyzed using the Shannon–Wiener diversity index and Non-Metric Multidimensional Scaling (nMDS) ordination analysis with the Bray–Curtis index. The results showed that a total of 696 individual birds were recorded, comprising 30 species from 7 orders. The highest number of individuals was found in the lake riparian ecosystem (293), followed by lowland forest (267) and coastal areas (136). The highest diversity index value was observed in the lowland forest ecosystem (H’ = 2.52), followed by the lake riparian (H’ = 2.51), and the lowest in the coastal ecosystem (H’ = 2.46). The composition of feeding guilds was dominated by insectivores (31%) and omnivores (24%). The nMDS results indicated overlap in bird communities across ecosystems, suggesting flexible habitat use. Habitat diversity in Napabale Lake plays an important role in maintaining the stability of the bird community and has potential for development as birdwatching ecotourism.